170k views
3 votes
Can you help me with questions no 13 only part b

Can you help me with questions no 13 only part b-example-1
User Liang
by
4.8k points

1 Answer

3 votes

To answer this question, we need to use the binomial theorem, and we have the identity when we raise the binomial to 4:


(a+b)^4=a^4+4a^3b+6a^2b^2+4ab^3+b^4

And we also have that:


(a-b)^4=a^4-4a^3b_{}+6a^2b^2-4ab^3+b^4

And now, we know that the values for a and b are:


a=\sqrt[]{5},b=\sqrt[]{2}

Then, we also know that we need the result for:


(a+b)^4+(a-b)^4

Then, if we substitute the equivalent expressions, we have:


(a^4+4a^3b+6a^2b^2+4ab^3+b^4)+(a^4-4a^3b_{}+6a^2b^2-4ab^3+b^4)

Simplifying, we have - we need to add the like terms as follows:


a^4+a^4+4a^3b-4a^3b+6a^2b^2+6a^2b^2+4ab^3-4ab^3+b^4+b^4

Therefore:


2a^4+2(6a^2b^2)+2b^4=2a^4+12a^2b^2+2b^4

We see that some terms were canceled since they are the same with opposite signs:


\begin{gathered} 4a^3b-4a^3b=0 \\ 4ab^3-4ab^3=0 \end{gathered}

Now, we can substitute the values for a and b as follows:


a=\sqrt[]{5},b=\sqrt[]{2}

We need to remember that:


\sqrt[]{5}=5^{(1)/(2)},\sqrt[]{2}=2^{(1)/(2)}

Then we have:


2(5^{(1)/(2)})^4+12(5^{(1)/(2)})^2(2^{(1)/(2)})^2+2(2^{(1)/(2)})^4

Thus


2(5^{(4)/(2)})+12(5^{(2)/(2)})(2^{(2)/(2)})+2(2^{(4)/(2)})
\begin{gathered} 2(5^2)+12(5)(2)+2(2^2) \\ 2(25)+12(10)+2(4) \\ 50+120+8=178 \end{gathered}

In summary, therefore, we have that:


(\sqrt[]{5}+\sqrt[]{2})^4+(\sqrt[]{5}-\sqrt[]{2})^4=178

User Prosunjit Biswas
by
4.8k points